Characterization of the interface between fresh concrete and formwork - Bouharoun, Samir (Journal of Civil Engineering and Management, 2015)
Concrete surface quality is generally linked to the development conditions of concrete close to the formwork. This work aims to study the influence of the nature of release agent and the quantity of fine elements on the chemical interactions at the concrete/oil/formwork interface. Five concretes were prepared at 28, 30, 32, 34, and 36% of paste to study the influence of paste volume on the friction between formwork and fresh concrete. The friction tests were performed using an apparatus which can reproduce the same conditions of construction sites. In addition, a physicochemical investigation was achieved to identify the effect of fine elements on the ability to form the interstitial mediums at the interface. The formation of soap in the vicinity of the formwork surfaces was also studied as a function of the content and the nature of oils. The results showed that the friction between fresh concrete and formwork depends on the pore solution content present at the interface.